In-Depth Study of the Interaction, Sensitivity, and Gating Modulation by PUFAs on K+ Channels; Interaction and New Targets - Moreno, Cristina; de la Cruz, Alicia; Valenzuela, Carmen (Frontiers in Physiology, 2016)
Voltage gated potassium channels (Kv) are membrane proteins that allow selective flow of K+ ions in a voltage-dependent manner. These channels play an important role in several excitable cells as neurons, cardiomyocytes and vascular smooth muscle. Over the last 20 years, it has been shown that omega-3 polyunsaturated fatty acids (PUFAs) enhance or decrease the activity of several cardiac Kv channels. PUFAs-dependent modulation of potassium ion channels has been reported to be cardioprotective. However, the precise cellular mechanism underlying the cardiovascular benefits remained unclear in part because new PUFAs targets and signaling pathways continue being discovered. In this review, we will focus on recent data available concerning the following aspects of the Kv channel modulation by PUFAs: i) the exact residues involved in PUFAs-Kv channels interaction; ii) the structural PUFAs determinants important for their effects on Kv channels; iii) the mechanism of the gating modulation of KV channels and, finally, iv) the PUFAs modulation of a few new targets present in smooth muscle cells, KCa1.1, K2P and KATP channels, involved in vascular relaxation.